WHISTLEBLOWER’S REGULATION – LEGAL AND ETHICAL PERSPECTIVES ON EU DIRECTIVE TRANSPOSITION INTO NATIONAL LAW - BORA, Alexandrina-Augusta (Studia Universitatis Babeș-Bolyai Philosophia, 2022)
This article is analysing the legal perspective on whistleblowing, at European and national level, focusing on the scientific studies’ results and theories, emphasizing nuances which worth discussing in order to a better understanding of the social phenomenon and of individual psychological decision process for reporting a wrongdoing or the suspicion of a possible breach. We are also arguing that current whistleblower regulations must take into account both the European directive and recent research in this field, pointing out some question which are raising from the lack of the ethical and cultural focused research of Romanian society perspective on whistleblowing, considering also the recent past experiences of Romanians with political police actions in years of communism. We are establishing a few research directions which we conclude that could bring the knowledge to drawing a more relevant and applicable whistleblowing law.